The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1159/000514507
|View full text |Cite
|
Sign up to set email alerts
|

Clinicogenetic Profile, Treatment Modalities, and Mortality Predictors of Gaucher Disease: A 15-Year Retrospective Study

Abstract: <b><i>Introduction:</i></b> Gaucher disease (GD) is a rare autosomal recessive lysosomal storage disorder, in which biallelic pathogenic variants in the Glucosidase beta acid (<i>GBA</i>) gene result in defective functioning of glucosylceramidase that causes deposition of glucocerebroside in cells. GD has 3 major types namely, non-neuronopathic (type I), acute neuronopathic (type II), and chronic neuronopathic (type III). Definite treatment options are limited and expensive.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
(28 reference statements)
0
5
1
Order By: Relevance
“…Our result suggested that mutation spectrum of GBA in Thai patients was more homogeneous than ever believed and was different from those seen in Caucasian populations, and more similar to those of East Asian descendants [ 4 , 6 , 11 , 13 , 15 17 , 22 ].…”
Section: Discussioncontrasting
confidence: 48%
“…Our result suggested that mutation spectrum of GBA in Thai patients was more homogeneous than ever believed and was different from those seen in Caucasian populations, and more similar to those of East Asian descendants [ 4 , 6 , 11 , 13 , 15 17 , 22 ].…”
Section: Discussioncontrasting
confidence: 48%
“…Our result suggested that mutation spectrum of GBA in Thai patients was more homogeneous than ever believed and was different from those seen in Caucasian populations, and more similar to those of East Asian descendants [3,5,10,12,[16][17][18]21].…”
Section: Discussionmentioning
confidence: 72%
“…In this context, treatment with iron supplementation and, in some cases, an antifibrinolytic agent, may be necessary. Treatment with oral contraceptives is considered a good therapeutic option for young patients with menorrhagia [ 4 ]. Increased menstrual bleeding associated with intrauterine devices (IUDs) has been reported in up to 50% of patients, especially if associated with severe disease [ 9 ].…”
Section: Childhood and Adolescencementioning
confidence: 99%
“…In contrast, eliglustat is a first-line treatment, like ERT, and is applicable to all patients with GD1 who are not ultra-rapid metabolizers of cytochrome CYP2D6 [ 3 ]. These treatments have increased the survival and the quality of life of the patients [ 4 ].…”
Section: Introductionmentioning
confidence: 99%

Women with Gaucher Disease

Meijon-Ortigueira,
Solares,
Muñoz-Delgado
et al. 2024
Biomedicines